Analisis Komparatif Keamanan dan Kinerja Protokol Komunikasi pada Web of Things: Tinjauan Sistematis terhadap HTTP, CoAP, dan MQTT - Faid Rama Daniy; Mirza Putra Firmansyah; Arief Muhammad Luthfi Yanuar; Putri Safira Augusta; Arief Arfriandi (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The integration of the Internet of Things (IoT) into the Web of Things (WoT) offers cross-platform interoperability but presents significant security challenges for constrained devices. This study aims to evaluate the effectiveness and efficiency of security mechanisms in three major WoT protocols: HTTP, CoAP, and MQTT. The research methodology employs a Systematic Literature Review (SLR) following PRISMA guidelines, reviewing 22 selected articles published between 2020 and 2025. The analysis utilizes PICOC criteria to compare communication overhead, computational consumption, and security mechanisms such as DTLS, OSCORE, and TLS integration. The results indicate that CoAP, combined with OSCORE and EDHOC mechanisms, provides the optimal balance between energy efficiency and end-to-end security for resource-constrained devices. MQTT demonstrates superiority in throughput and data transmission speed but requires additional security layers to ensure data confidentiality. Meanwhile, HTTP dominates in terms of Web service integration and access control, despite having the highest overhead burden. In conclusion, no single protocol is superior for all scenarios; the choice of protocol in WoT architecture must be based on the trade-offs between latency, resource efficiency, and system security requirements